2015
DOI: 10.1109/jphot.2015.2472281
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Secrecy Capacity and Code Length Dependence of the Performances in Optical Wiretap Channels

Abstract: Secrecy issues of free-space optical links realizing information theoretically secure communications as well as high transmission rates are discussed. We numerically study secrecy communication rates of optical wiretap channel based on onoff keying modulation under typical conditions met in satelliteground links. It is shown that under reasonable degraded conditions on a wiretapper, information theoretically secure communications should be possible in a much wider distance range than a range limit of quantum k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…It has been verified that physical layer security (PLS) technology can prevent illegitimate receivers from eavesdropping due to the time-varying nature of the wireless medium [4]- [8]. Numerical studies of PLS over FSO satellite ground systems were performed by Endo et al [9]. They showed that secrecy communications were possible and that there can be a complementary technologies to balance security and usability issues.…”
mentioning
confidence: 99%
“…It has been verified that physical layer security (PLS) technology can prevent illegitimate receivers from eavesdropping due to the time-varying nature of the wireless medium [4]- [8]. Numerical studies of PLS over FSO satellite ground systems were performed by Endo et al [9]. They showed that secrecy communications were possible and that there can be a complementary technologies to balance security and usability issues.…”
mentioning
confidence: 99%
“…At this point it's necessary to reference a numerical study conducted by the Sasaki research team in Japan wherein they reported secrecy capacity and secure key rate performance when using channel codes in an optical wiretap scenario for geostationary satellite to ground links. Taking into account power and bandwidth constraints and using channel attenuation as the main degradation source, they showed that information-theoretic secure communications could be possible at very long distances [13]. This work was followed by a very recent series of comprehensive experimental demonstrations of secure message transmissions over a metropolitan 7.8 km terrestrial FSO link in the presence of an eavesdropping attack [14]- [16].…”
Section: Optical Wiretap Channel Scenariomentioning
confidence: 99%
“…Analysis results show that the joint effect of laser-beam divergence and turbulence-induced fading on the received irradiance allows an external Eve close to the legitimate receiver to compromise the communication. Secrecy issues of FSO links realizing information-theoretic security and high transmission rates are discussed in [13]. It is shown that, under reasonable degraded conditions, information theoretically secure communications should be possible in a much wider distance range than the range limit of quantum key distribution.…”
Section: Introductionmentioning
confidence: 99%